Optimalisasi Pendampingan Belajar Home Learning di Era Pandemi Covid-19 di Binalatung Pantai Amal Kota Tarakan - Nurmala R (Rengganis Jurnal Pengabdian Masyarakat, 2021)
The Home Learning program during the COVID-19 pandemic is a community service activity in theimplementation of the tri dharma of higher education at the University of Borneo Tarakan. This serviceactivity is carried out to increase learning motivation and student interest in learning at school. The impactof the COVID-19 pandemic is enormous in the education sector. The difficulties experienced by parents ofstudents at Binalatung Pantai Amal is when accompanying their children with inadequate facilities andabilities, one of which is that parents are busy in their daily activities to earn a living as fishermen andseaweed farmers. Therefore, to help the parents of these students also stay at home to decide thetransmission of covid-19, we held a home learning program as a community service activity, and the objectswere students in Binalatung. The learning mentoring method used is to provide offline learning assistancein the form of small groups consisting of 5 people in each study group. The mentoring process went well andsmoothly. The results obtained from the study assistance at the charity beach Binalatung are quite good.Students are very enthusiastic during the learning mentoring process and feel helped in completingassignments at school.